Economic Growth The New Perspectives for Theory and Policy - Kim, Tai-Yoo.; Heshmati, Almas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book shows that the existing theories on economic growth have clear limitations in terms of how much they can effectively contribute to actual economic growth. Therefore, this book presents a more effective theory on economic growth for countries and leaders looking to promote economic growth. It is essentially centered around the theory of economic growth and theory of national development, written for agricultural developing countries pursuing industrialization and late-starting industrialized countries pursuing their own development. Nevertheless, it also makes a significant contribution to the very development of human civilization through the growth of developing countries, late-starting industrialized countries and early industrialized countries throughout the world.
Preface -- Introduction to and Summary of Economic Growth: Perspectives on New Theory and Policy -- Decelerating Agricultural Society: Theoretical and Historical Perspectives -- Accelerating Economic Growth in Industrial Societies: The Process of Expansive Reproduction -- Determinants of Economic Divergence among Accelerating Societies -- The Faster-Accelerating Digital Economy -- The Faster Accelerating Growth of the Knowledge-Based Society -- The Catch-Up Illusion: Why Developing Nations that Experience Rapid Economic Growth Can Never Catch Up with Advanced Countries -- War, Peace and Economic Growth: The Phoenix Factor Reexamined -- The Relationship Among Stock Markets, Banks, Economic Growth, and Industry Development -- The Necessity of a New Industrial Classification Based on Value-Creation Behavior -- Biography of the Authors.
Keywords: Economics; Endogenous growth (Economics).; Economic policy; Social sciences; Economics/Management Science; Economic Growth; Social Sciences, general; Economic Policy